The Immune Enhancement of Sodium Lauryl Sulfoacetate in Chickens - DaRong Cheng; ShanYuan Zhu; HuaiChang Sun (Veterinary Medicine International)
The purpose of this study is to investigate feasibility of sodium lauryl sulfoacetate (SLS) as an immunoadjuvant in chickens. After treating with 62.5, 125, 250, or 500 μg/mL SLS in vitro, lymphocyte proliferation assay of chicken peripheral blood mononuclear cells showed that the OD570 values of all experimental groups, as well as Con A-stimulated group, were significantly higher than that of the untreated control group. After injection with 1.0, 2.0, or 4.0 mg/kg of SLS for 3 consecutive days, chickens were vaccinated with an attenuated vaccine against Newcastle disease virus (NDV), and the immunoadjuvant effects of SLS were evaluated on the basis of immune organ index, antibody response, and CD4+/CD8+ T-cell ratio. The results confirmed that SLS could enhance NDV-specific antibody response and increase CD4+/CD8+ T-cell ratio in vivo. Furthermore, SLS could improve NDV-specific antibody response in thiamphenicol-treated chickens. These data indicate that SLS not only can improve humoral immune response but also reverse the immunosuppressive effect of thiamphenicol in chickens.